2010
DOI: 10.1177/026119291003800110
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation of the Extent of Animal Use in Research in Brazil, as Determined by Bibliographic Sampling from Journals Published in the State of Paraná

Abstract: Animal use in research is an issue of increasing ethical concern. The objective of this work was to investigate animal use in research described in the papers appearing in 18 journals published in the State of Paraná in 2006. The fields used in the bibliographic sampling were: agrarian science, biological science, biological and health science, environmental science, food technology, and health science. Of the 865 papers analysed, 41% involved the use of animals — a total of 3,497,653 animals, of which 216,223… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…Brazil is progressing towards the collection and maintenance of an official register of the numbers of animals used in laboratories, but this facility is not yet available. Given this information gap, bibliographic sampling from 18 scientific journals published in the State of Paraná in 2006 19 suggested that 216,223 vertebrate animals had been used in laboratory experiments. This number was derived from a sample of 42% of the relevant journals in a single Brazilian state (out of 26), which stands in fifth position regarding national scientific output.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil is progressing towards the collection and maintenance of an official register of the numbers of animals used in laboratories, but this facility is not yet available. Given this information gap, bibliographic sampling from 18 scientific journals published in the State of Paraná in 2006 19 suggested that 216,223 vertebrate animals had been used in laboratory experiments. This number was derived from a sample of 42% of the relevant journals in a single Brazilian state (out of 26), which stands in fifth position regarding national scientific output.…”
Section: Resultsmentioning
confidence: 99%
“…In the United Kingdom, 17 most procedures are classified as mild and moderate (equivalent to CONCEA DI 2 and DI 3) and only 6% of procedures are classified as severe (equivalent to CONCEA DI 4). Furthermore, Bones et al 19 analysed the DI values of animal procedures carried out for research purposes in the State of Paraná, Southern Brazil, and also found that the CCAC classifications B and C (equivalent to CONCEA DI 1 and DI 2) were the most frequent, with around 4% of the procedures on vertebrates being considered to be DI E (equivalent to CONCEA DI 4). When comparing the DI values stated by the respondents and the DI values after reclassification, a Kendall coefficient of concordance W ( t ) = 0.799 W ( p = 0.000334) was observed, showing a significant agreement between the DIs attributed by the respondents and by us.…”
Section: Resultsmentioning
confidence: 99%
“…It is estimated that 58,339,972 laboratory animals were used in 2005, taking into account the available data from 179 countries (23). Brazil seems important in this context, in terms of total numbers and in terms of vertebrate animals (24). For rabies diagnosis, in a laboratory that performs 200 MITs per month and inoculates eight mice per sample, the number of animals used would be around 19,200 per year.…”
Section: Cell Culture Can Be Expensive Requires Biosafety Cabinets Amentioning
confidence: 99%
“…A experimentação animal visa a demonstrações didáticas, testes de toxicidade, produção de vacinas e medicamentos, avaliações de mecanismos orgânicos e fisiológicos, bem como a produção de animais transgênicos, knockouts e clones (Paixão & Schramm, 1999, Magalhães & Ortêncio-Filho, 2006. Diante dessa demanda, surgiu a preocupação do reflexo do modelo animal e de seu bem-estar na qualidade e veracidade das pesquisas, aprimorando a área de ciência de animais de laboratório e sua consequente sanidade, manejo, genética, bem-estar, enriquecimento ambiental e educação (Baumans, 2004;Frajblat, 2007;Marques, Miranda, Caetano & Biondo-Simões, 2005;Silla, Sans & Molento, 2010;Sogayar, 2006), sendo constituído em 1993 o Colégio Brasileiro de Experimentação Animal (Cobea) a fim de estimular a conscientização no uso de animais em experimentação (Sogayar, 2006). No final do século XX, a sociedade passou a questionar os procedimentos éticos nas experimentações, tanto para pesquisas científicas quanto industriais, e os alunos passaram a ter sensações negativas diante dos animais usados nas aulas (Luna, 2008;Tréz & Nakada, 2008).…”
Section: O Uso Dos Animais Na Experimentaçãounclassified